Metode Pengembangan Perangkat Lunak MDLC Pada Rancang Bangun Media Pembelajaran Planet Berbasis Teknologi Augmented Reality - Supriyono, Abdul Rohman; Dwi Fatimah, Anggita; Bahroni, Isa; Perdana Wanti, Linda; Nur Faiz, Muhammad (Infotekmesin, 2023)
Along with the development of smartphones, Augmented Reality technology has begun to be used as a medium of interaction, although it has not been properly implemented and applied as a supporting medium. The use of still image objects in textbooks can make students tend to be more passive and less interactive because media images are unable to provide a reciprocal response. In science subjects, there is solar system material regarding planet recognition. Props are needed as learning media because the object of observation from the planet is too large. Several props are used as imitations of the planets, such as the use of drawing paper, audio, and video. The purpose of this research is to make a breakthrough in the use of Augmented Reality technology to support media for understanding planet recognition material by creating digital teaching aids that can be installed on smartphone devices. The MDLC method is an alternative method for developing multimedia applications that are easy to understand. The results of the test show that the application can function as expected, where each planetary marker that has been made can be recognized properly according to the intended planetary object.